Totally extraperitoneal repair using three midline ports versus enhanced view totally extraperitoneal repair in men with uncomplicated inguinal hernia - Arshad Rashid; Rajandeep Singh Bali; Abdul Hamid Samoon; Refut Arah; Satbir Singh; Iqbal Saleem Mir (International Journal of Abdominal Wall and Hernia Surgery, 2023)
AIM: The aim of this study was to compare the “totally extra-peritoneal” repair (TEP) using three midline ports with “enhanced view totally extra-peritoneal repair” (eTEP) repair in the management of inguinal hernia. MATERIALS AND METHODS: This was a retrospective study conducted in a tertiary care hospital by analyzing a prospectively maintained database over a period of 3 years. Data from 152 patients with inguinal hernias were analyzed who were operated in equal numbers, either by TEP repair or by eTEP repair. Follow-up data of 1 year were also analyzed. In the TEP group, five patients, and in the eTEP group, four patients had not completed the mandatory 1-year follow-up and as such were excluded from the final analysis. Thus, the total number of patients considered for final analysis was 143 (TEP [71], eTEP [72]). RESULTS: The average operative time in TEP repair using three midline ports was 68.16 minutes and that in eTEP repair was 65.12 min (P = 0.4321). No statistically significant difference was noted in the intraoperative and postoperative complication rates between these two techniques. The Surgeon’s Satisfaction Score was significantly better in the eTEP group as compared to the TEP group (P = 0.0023). The recurrence rates (P = 0.7861) and postoperative hospital stay were not different between the two techniques (P = 0.7125). CONCLUSION: In experienced hands, both TEP and eTEP provide similar results; however, eTEP provides an overall better surgeon satisfaction score.